D’Emma Bovary à Gemma Bovery : une approche traductologique - Ilaria Vitali (Flaubert: Revue Critique et Génétique)
Gemma Bovery by Posy Simmonds is one of the most studied rewritings of Madame Bovary. Among the various ways of looking at this graphic reinterpretation of Flaubert’s novel, I will adopt a translational perspective. The reading I propose in this article is based on Roman Jakobson’s well-known concept of “intersemiotic translation” and seeks to read Gemma Bovery with the tools of “translation criticism”, a branch of translation studies. Within this field, the interpretive paradigm will be the one proposed by Lance Hewson, based on two levels: the “voice effects” (translational choices that modify the voice of the narrator or characters), and the “interpretational effects” (translational choices that favour different interpretive paths). The horizon of my research will first concern the micro and meso-textual levels (i.e., punctual choices), in order to better appreciate the macro-structural level (strategic choices). At the theoretical level, it will be a matter of seeing what contribution the tools of translation studies can make to the analysis of a rewriting.